Study of structural stability of a concrete gravity dam using a reliability approach - Mohamed Essaddik Kerkar; Mustapha Kamel Mihoubi (Fracture and Structural Integrity)
Dam safety is a priority at the international level, it requires a large amount of data that allows analysts to make optimization on its structural stability, the latter is based on the estimation of the probability of failure from the effects of stress and resistance acting on the dam-reservoir system. This investigation is to establish a methodology in order to optimize the safety of a concrete gravity dam in operation by carrying out a risk analysis which includes the identification of the sources of danger in terms of scenarios that can occur due to a failure on the dam-reservoir system on an implication of natural hazards (floods, earthquakes) and technical accidents such as malfunction of a spillway gate, drain valve, drainage system or important silting. Reliability methods provide a basis for the probabilistic assessment of the structural safety of a dam. They make it possible to take into account in a probabilistic context, the uncertainties in the data associated with the calculation parameters used in the justifications of structural stability and make it possible to assess as closely as possible the intrinsic safety of a concrete gravity dam.